2020
DOI: 10.1158/0008-5472.can-18-3539
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evolution of Epithelial–Mesenchymal Transition in Human Carcinomas

Abstract: The significance of the phenotypic plasticity afforded by epithelial-mesenchymal transition (EMT) for cancer progression and drug resistance remains to be fully elucidated in the clinic. We evaluated epithelial-mesenchymal phenotypic characteristics across a range of tumor histologies using a validated, highresolution digital microscopic immunofluorescence assay (IFA) that incorporates b-catenin detection and cellular morphology to delineate carcinoma cells from stromal fibroblasts and that quantitates the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 65 publications
(69 reference statements)
3
63
0
Order By: Relevance
“…However, BC cells can employ a variety of mechanisms to escape cell death induced by chemotherapeutic drugs. These mechanisms mainly include the efflux and inactivation of drugs 20 , activation of bypass signaling or prosurvival pathways, enhancement of DNA damage repair 21 , and induction of epithelial-mesenchymal transition (EMT) 22 and stem-like property 23 . Also, a large body of evidence demonstrated that the content of exosomes secreted by tumor cells changes in response to cellular stress induced by anticancer therapy, resulting in the transfer of drug-resistant phenotypes among tumor cells in BC [24][25][26] .…”
Section: Exosome and Chemoresistance In Bcmentioning
confidence: 99%
“…However, BC cells can employ a variety of mechanisms to escape cell death induced by chemotherapeutic drugs. These mechanisms mainly include the efflux and inactivation of drugs 20 , activation of bypass signaling or prosurvival pathways, enhancement of DNA damage repair 21 , and induction of epithelial-mesenchymal transition (EMT) 22 and stem-like property 23 . Also, a large body of evidence demonstrated that the content of exosomes secreted by tumor cells changes in response to cellular stress induced by anticancer therapy, resulting in the transfer of drug-resistant phenotypes among tumor cells in BC [24][25][26] .…”
Section: Exosome and Chemoresistance In Bcmentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) often precedes, and in model systems has been shown to promote, tumor invasiveness and metastasis [40]. Concurrent overexpression of TKs and a set of EMT TAs that they regulate was used as a proxy of oncogenic TK pathway activation in samples from the BCa TCGA dataset [21].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical work also suggests that EMT contributes to drug resistance by increasing cancer stem cell (CSC) markers. Treatment of a patient with metastatic prostate cancer with the PARP inhibitor talazoparib increased NANOG, CD133, CD44v6, and ALDH1, which are CSC markers [44] . TGF-β1-induced EMT increases ALDH expression and leads to the generation of CSCs.…”
Section: The Role Of Emt In Tumour Immune Evasion and Drug Resistancementioning
confidence: 98%